SCIENCE AND TECHNOLOGY BASED COMPANY, ITS FEATURES AND RELATIONS TO ENVIRONMENT - Adamauskas, Saulius; Krusinskas, Rytis (Economics and Management, 2013)
According to different authors, science and technology based companies could be considered as a crucial chain in transforming research and development investments into economic value. This could impact company’s business performance and at the same time the development of country’s economy. Moreover, according to today’s empirical research, extremely fast innovation and technology development all over the world has a different effect on separate industries. There is a lot of academic literature where science and technology based company environment assessment issues are described, however, there is a lack of assessment methods and/or ratios/indicators, which show how the company is science, innovation and technology based and even how to identify such kind of company. This article is divided into structural parts, reflecting: R&D environment analysis based on the case of Lithuania; academic literature overview regarding science and technology based company’s environment analysis; definition of S&T based company economic/financial assessment ratios. After the analysis, a list of ratios/indicators were presented, which empower to identify and/or asses such kind of company. Data availability was the core factor in these indicators creation processes. Research methods used are based on systematic literature analysis, mathematical statistics methods, logical comparative and generalization analysis.
Keywords: Data; Libre accès; Processus de création; Statistiques

SCIENCE AND TECHNOLOGY BASED COMPANY, ITS FEATURES AND RELATIONS TO ENVIRONMENT - Adamauskas, Saulius; Krusinskas, Rytis (Economics and Management, 2013)
According to different authors, science and technology based companies could be considered as a crucial chain in transforming research and development investments into economic value. This could impact company’s business performance and at the same time the development of country’s economy. Moreover, according to today’s empirical research, extremely fast innovation and technology development all over the world has a different effect on separate industries. There is a lot of academic literature where science and technology based company environment assessment issues are described, however, there is a lack of assessment methods and/or ratios/indicators, which show how the company is science, innovation and technology based and even how to identify such kind of company. This article is divided into structural parts, reflecting: R&D environment analysis based on the case of Lithuania; academic literature overview regarding science and technology based company’s environment analysis; definition of S&T based company economic/financial assessment ratios. After the analysis, a list of ratios/indicators were presented, which empower to identify and/or asses such kind of company. Data availability was the core factor in these indicators creation processes. Research methods used are based on systematic literature analysis, mathematical statistics methods, logical comparative and generalization analysis.
Keywords: Data; Libre accès; Processus de création; Statistiques